GE_GERICHTE P/13551/2008 vom 14. Januar 2015 - GE Cour de justice (2015)
LÉSION CORPORELLE PAR NÉGLIGENCE; ENQUÊTE PÉNALE; PRESCRIPTION; SUSPENSION DU DÉLAI; RÉVISION(DÉCISION) | CPP.136; CPP.319; CPP.323; CPP.410; CP.97